Hubungan Antara Beban Kerja Dengan Stres Kerja Karyawan PT. Jasa Pengiriman Barang Cabang Medan Katamso - Butar-Butar, Al-Hilmi NoorBamela; Aziz, Azhar (Universitas Medan Area, 2025)
This study is to determine the correlation between workload and work stress on each employee because each employee has limited abilities both physically and mentally to the workload given by the company. This research method uses quantitative methods. The population and sample in this study were all employees of PT. Delivery Service for Medan Katamso branch for the Last Mile division of SDS (Same Day Service), COD (Cash On Delivery) and Regular, totaling 30 people, the sampling technique in this study used the Total Sampling technique. The data collection method in this study used the workload scale and work stress scale. The data analysis technique uses the Product Moment correlation technique from Karl Pearson, seen from the coefficient value (Rxy) which has a value of 0.549 with a p or significance of 0.000 0.050, which means that there is a positive and significant correlation between workload and work stress on employees of PT. Delivery Service Medan Katamso branch with a determinant coefficient value (r2) which has a value of 0.301, with a contribution of 30.1%. In other words, the hypothesis is accepted. The workload is classified as high (empirical mean = 60.93 hypothetical mean = 50 where the difference is more than SD = 6.016), and for work stress it is high (empirical mean = 90.10 hypothetical mean = 75 where the difference is more from saying SD = 11.848).